2018
DOI: 10.1038/s41598-018-32220-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of precise measurements of natural radionuclides and radiation dose using in-situ and laboratory γ-ray spectroscopy techniques

Abstract: In this study, in-situ and laboratory γ-ray spectroscopy techniques were compared to evaluate the activity concentration of natural radionuclides in soil. The activity concentrations of U (Ra), Th, andK in the soil in 11 sites were simultaneously measured with in-situ portable HPGe and the NaI(Tl) detectors. In parallel, 55 soil samples collected from these sites were analyzed with a laboratory γ-ray spectroscopy technique (HPGe). A strong correlation was observed between the in-situ and laboratory HPGe techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…A weak correlation was observed between the activity concentrations of 226 Ra and 232 Th with a correlation coefficient of r 2 = 0.51. No correlation was observed between the measured radionuclides 232 Th and 40 K and 226 Ra and 232 Th (Fig 12) Authors have observed contrasting correlation among the radionuclides (Kovacs et al 2013;Baeza et al 2016, Hassan et al 2018 however in this case it indicates that these radionuclides 226 Ra , 232 Th and 40 K are of different geochemical origin.…”
Section: Correlation Studies Between the Individual Radionuclidesmentioning
confidence: 82%
“…A weak correlation was observed between the activity concentrations of 226 Ra and 232 Th with a correlation coefficient of r 2 = 0.51. No correlation was observed between the measured radionuclides 232 Th and 40 K and 226 Ra and 232 Th (Fig 12) Authors have observed contrasting correlation among the radionuclides (Kovacs et al 2013;Baeza et al 2016, Hassan et al 2018 however in this case it indicates that these radionuclides 226 Ra , 232 Th and 40 K are of different geochemical origin.…”
Section: Correlation Studies Between the Individual Radionuclidesmentioning
confidence: 82%
“…The ranges of the activity concentrations of 238 U, 232 Th, and 40 K were 6.055-72.86 Bq/kg, 19.48-95.81 Bq/kg, and 287.96-1633.86 Bq/kg for the in-situ measurements, and 6.71-70.89 Bq/kg, 16.08-83.62 Bq/kg, and 208.72-1262 Bq/kg in the laboratory, respectively. The determined radionuclide activity concentrations were compared with studies in the literature for similar rock types [63][64][65][66][67]. As a result, no significant difference was found between in-situ and laboratory measurements.…”
Section: Laboratory Gamma Spectrometry Analysis Of Samples Collected ...mentioning
confidence: 99%
“…It is possible to find in scientific publications several studies on the evaluation of external (environmental) dose rates on different types of surfaces [17][18][19]. Several methods and detectors allow the quantification and detection of radiation [20].…”
Section: Introductionmentioning
confidence: 99%